2005
DOI: 10.1002/jcc.20259
|View full text |Cite
|
Sign up to set email alerts
|

Conformations, energies, and intramolecular hydrogen bonds in dicarboxylic acids: Implications for the design of synthetic dicarboxylic acid receptors

Abstract: The various conformers of the dicarboxylic acids HO2C--(CH2)n--CO2H, n = 1-4, were obtained using density functional methods (DFT), both in the gas phase and in the aqueous phase using a polarized continuum model (PCM). Several new conformers were identified, particularly for the two larger molecules glutaric (n = 3) and adipic acid (n =4). The PCM results show that the stability of most conformers were affected, many becoming unstable in the aqueous phase; and the energy ordering of conformers is also differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Glutaric acid [(CH 2 )n(COOH) 2, n = 3] in the present work as compared to malonic acid [(CH 2 )n(COOH) 2, n = 1], appears to be the reason for the enhanced water uptake of the polyurethanes. It has been reported that the most stable conformer (∆G = 0) of glutaric acid in water has greater dipole moment ( p glutaric = 4.66 D) than that of malonic acid conformer in water ( p glutaric = 3.68 D) [ 70 ]. Glutaric acid has a greater dipole moment, indicating that the hydrogen bond acceptor C=O has higher electronegativity than that of malonic acid, hence polyurethanes comprising of glutaric acid in the soft segment are hypothesized to have stronger hydrogen bonding energy, thus exhibiting superior water uptake during the enzymatic degradation test ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Glutaric acid [(CH 2 )n(COOH) 2, n = 3] in the present work as compared to malonic acid [(CH 2 )n(COOH) 2, n = 1], appears to be the reason for the enhanced water uptake of the polyurethanes. It has been reported that the most stable conformer (∆G = 0) of glutaric acid in water has greater dipole moment ( p glutaric = 4.66 D) than that of malonic acid conformer in water ( p glutaric = 3.68 D) [ 70 ]. Glutaric acid has a greater dipole moment, indicating that the hydrogen bond acceptor C=O has higher electronegativity than that of malonic acid, hence polyurethanes comprising of glutaric acid in the soft segment are hypothesized to have stronger hydrogen bonding energy, thus exhibiting superior water uptake during the enzymatic degradation test ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…In malonic acid, the labile, non-H-bonded acidic hydrogen could participate in reaction with a Criegee intermediate, whereas larger dicarboxylic acids have two labile acidic hydrogens, but lower dipole moments. 32 Thus, the reactivity of the dicarboxylic acids is expected to be similar to regular carboxylic acids. However, dicarboxylic acids have low vapour pressures; for example, Malonic acid has a vapour pressure of 9.8  10 -7…”
Section: Kinetics Of Criegee Intermediate + Carboxylic Acid Reactionsmentioning
confidence: 99%
“…Similar to the PepT1 substrates, the dicarboxylates transported by NaDC1 are flexible molecules that can adopt multiple stable conformations [22,23]. The differences in the substrate binding pockets between the rabbit and mouse NaDC1 are probably the result of differences in substrate:protein contact points or differences in the size of the substrate binding pocket.…”
Section: Discussionmentioning
confidence: 99%